Cell Delivery: Enhanced In Vivo Delivery of Stem Cells using Microporous Annealed Particle Scaffolds (Small 39/2019). Issue 39 (25th September 2019) - Koh, Jaekyung; Griffin, Donald R.; Archang, Maani M.; Feng, An‐Chieh; Horn, Thomas; Margolis, Michael; Zalazar, David; Segura, Tatiana; Scumpia, Philip O.; Di Carlo, Dino
Abstract : In article number 1903147, Philip O. Scumpia, Dino Di Carlo, and co‐workers co‐inject microgel particles with cells, which are covalently linked in situ to form a microporous scaffold for enhanced cell therapies.